Síntese e caracterização de três cimentos hidráulicos à base de silicato: análise de propriedades físico-químicas, biológicas e da influência da granulação - Aguiar, Bernardo Almeida (2023)
The possibility of repairing damaged dental structures has led the scientific community and companies in the sector to develop biocompatible mineral products, justifying such efforts by the potential to create different compositions of silicates. This work was divided into two studies. Regardless of the analysis, whether parametric or nonparametric in nature, the data were evaluated using ANOVA and Tukey tests, or Kruskal-Wallis and Dunn tests, respectively, with a significance level of 5%. The first study aimed to synthesize and characterize experimental hydraulic cements (CIEs) based on tricalcium silicate (C3S), calcium and zirconium silicate (CZS), and strontium phosphate silicate (SPS), comparing them with Biodentine cement. Characterization through Fourier-transform infrared spectroscopy (FTIR) determined the main chemical bond bands. X-ray diffraction (XRD) revealed standard peaks of C3S, CZS, and SPS as documented in the literature. Scanning electron microscopy (SEM) showed a granular morphology, and energy-dispersive X-ray spectroscopy (EDS) confirmed the absence of contaminating elements. Transmission electron microscopy (TEM) displayed the characteristics and average size of C3S (12 nm), CZS (55 nm), and SPS (46 nm) crystallites. Regarding the physicochemical properties, significant differences were observed in the initial and final setting time between BD<C3S and CZS; and SPS<C3S (P < 0.05). In terms of radiopacity, the materials were ranked as SPS>CZS>BD>C3S (without radiopacifier) and SPS>CZS>C3S>BD (with radiopacifier) (P < 0.05), with no significant differences in dimensional stability at 24 hours and 30 days (P > 0.05). In compressive strength, at 24 hours and 30 days, significant differences were observed between BD and the other cements (P < 0.05), with BD showing the highest values (141.53 and 91.81). In solubility, at 24 hours, BD presented the lowest mass loss (P < 0.05), as well as between C3S and CZS/SPS (P < 0.05). At 30 days, BD showed the lowest mass loss for C3S/SPS (P < 0.05). For pH, at 3 hours and 15 days, BD>C3S/CZS (P < 0.05). No differences were observed between the groups at 24 hours and 30 days (P > 0.05). At 72 hours, C3S>SPS/BD (P < 0.05). At 168 hours, C3S>CZS/BD (P < 0.05). In terms of calcium/strontium ion release, at 3 hours, SPS<C3S/CZS/BD (P < 0.05). In the other periods, SPS>C3S/CZS (P < 0.05). Regarding biocompatibility, there were no significant differences between the groups in the analyzed periods for polymorphonuclear cells, mononuclear cells, and fibroblasts (P > 0.05); there was lower vascularization at 30 days for BD/C3S/CZS (P < 0.05). The second study aimed to evaluate the influence of reducing the particle size of C3S. SEM images analyzed the average grain size after maceration in a mortar (CS) or grinding in a planetary mill (CSM). Median sizes were 0.816 μm (CS) and 0.322 μm (CS-M), with a 41% variation in grain size. CS and CS-M had initial setting times of 40' and 56', respectively (P < 0.05); both had final setting times of 75' (P > 0.05). In terms of radiopacity, CS had 8.56, and CS-M had 9.37 mm Al (P < 0.05). For pH, CS-M>CS at all time points, with significant differences observed at 3 and 24 hours (P < 0.05). In terms of calcium release, CSM>CS at 3, 24, and 72 hours (P < 0.05). Based on the results of this study, it can be concluded that CIEs showed similar physicochemical properties and biocompatibility, if not superior, to Biodentine cement, with the exception of setting time, compressive strength, and solubility. Furthermore, the reduction in particle size led to improvements in C3S characteristics, except for setting time. These findings, although requiring further validation studies, suggest promising prospects for their use as endodontic repair materials.